Model Pengaturan Plea Bargaining Dalam Pembaharuan Hukum Acara Pidana Indonesia - Henin Dyah Syafrina; Slamet Sudi Illahi; Bintang Pramadhani Hariadi Putra; Naura Tsurayya Hasnaa (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the regulatory model of plea bargaining under the 2025 Criminal Procedure Code and its implications for ensuring legal certainty and protecting defendants’ rights. This research constitutes normative legal research employing statutory, conceptual, and comparative approaches. The study is motivated by the enactment of the 2023 Criminal Code, which adopts a rehabilitative paradigm that is not yet fully aligned with the former Criminal Procedure Code, which is retributive in nature. This lack of alignment has resulted in inefficiencies in the criminal justice system and has exacerbated the problem of overcrowding in correctional institutions. The 2025 Criminal Procedure Code subsequently introduced a guilty plea mechanism as an instrument to enhance judicial efficiency; however, its regulatory framework still leaves several normative issues unresolved. The findings indicate that plea bargaining under the 2025 Criminal Procedure Code is characterized by a plea without bargain model with an active role of the judge. Nevertheless, it contains normative inconsistencies, particularly concerning disparities in sentencing thresholds, submission requirements, and the procedural design of the legal product resulting from summary examination proceedings, which is issued merely in the form of a “letter,” thereby creating uncertainty regarding available legal remedies. The novelty of this study lies in its prescriptive argument emphasizing the need to clarify the final legal form of the defendant’s admission within summary examination procedures, to harmonize sentencing limits, and to formulate technical regulations aimed at preventing abuse of authority and ensuring a balance between judicial efficiency and legal certainty within the framework of Indonesia’s new penal system. Penelitian ini bertujuan menganalisis model pengaturan plea bargaining dalam KUHAP 2025 serta implikasinya terhadap kepastian hukum dan perlindungan hak terdakwa. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif. Penelitian ini dilatarbelakangi oleh pemberlakuan KUHP 2023 yang berparadigma rehabilitatif belum sepenuhnya selaras dengan KUHAP lama yang retributif, sehingga menimbulkan ketidakefisienan peradilan pidana dan memperparah persoalan overcrowding lembaga pemasyarakatan. KUHAP 2025 kemudian memperkenalkan mekanisme pengakuan bersalah sebagai instrumen efisiensi, namun pengaturannya masih menyisakan persoalan normatif.  Hasil penelitian menunjukkan bahwa plea bargaining dalam KUHAP 2025 bercirikan plea without bargain dengan peran aktif hakim, tetapi mengandung inkonsistensi norma, khususnya terkait perbedaan batas ancaman pidana, syarat pengajuan, serta desain produk hukum acara pemeriksaan singkat yang hanya berbentuk “surat” dan menimbulkan ketidakjelasan upaya hukum. Kebaruan penelitian ini terletak pada argumentasi preskriptif mengenai kebutuhan penegasan bentuk akhir pengakuan terdakwa dengan acara pemeriksaan singkat, harmonisasi batas pemidanaan, serta perumusan regulasi teknis guna mencegah penyimpangan kewenangan dan memastikan keseimbangan antara efisiensi peradilan dan kepastian hukum dalam kerangka pemidanaan baru di Indonesia.